Affine versus projective transformation for SIFT and RANSAC image matching methods - Redzuwan R.; Radzi N.A.M.; Din N.M.; Mustafa I.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Edge detection; Image matching; Mathematical transformations; Affine transformations; Projective transformation; RANSAC; SIFT; SURF; Image processing